Liensinine can improve vascular remodeling in hypertension through the ferroptosis-related TLR4 inflammatory pathway - Daxin Chen; Peizhi Jia; Meiling Wang; Baojie Du; Haitao Du; Xi Huang; Jianwei Zeng; Qiaoyan Cai; Ling Zhang; Ying Zhu; Shan Lin; Dawei Lian; et al. (Journal of Molecular Medicine, 2026)

Oxygen-adaptive continuous lactate monitoring via dual-regime electrochemical sensing and dynamic calibration strategy - Xinyi Wang; Yuying Lin; Rubing Xiong; Jing Liu; Yue Liu; Zijie Li; Yongmei Chen; Yong Xia; Zhiqi Li; Lei Mou; Meiling Liu (Analytica Chimica Acta, 2026)

Inhibition of methane production in an alpine wetland of the Tibetan plateau by carbon-based nanomaterials - Chengfang Ma; Rong Wen; Miao Lin; Hongfei Chi; Meiling Feng; Pengfei Liu (Environmental Research, 2026)

Mild hydrolysis and upgrading utilization of waste PET: Preparation of regenerated TPA and MOF materials and study of their adsorption performance - Wei Lin; Meiling Zhang; Shun Zhang; Sheng Shi; Zeyu Wang; Chengyong Gao; Shuhua Wang; Enbin Zhu (Sustainable Chemistry and Pharmacy, 2026)

Bioinspired domed cone-pillar nanoarrays design for robust and low-haze-transparent superhydrophobic quartz glass - Yingying Dou; Yue Fan; Qiongwen Fu; Meiling Tao; Junyin Ouyang; Hongtao Liu; Lin Liu; Yabin Yang; Shilin Huang; Shan Zhou; Xuelin Tian (Chemical Engineering Journal, 2026)

Synergistic atomic-level anchoring and pore engineering of cobalt-nitrogen-carbon for anti-fouling and robust capacitive deionization - Huakun Pan; Haodong Zhang; Xinxi Teng; Yang Fan; Yaming Wang; Lin Li; Guisong Zhang; Meiling Liu; Haiou Song; Aimin Li; Shupeng Zhang (Chemical Engineering Journal, 2026)

Interleukin-12 Supports Self-renewal Division of Mouse Hematopoietic Stem Cells in Polyvinyl Alcohol-Based Culture - Jinglei Zhai; Xialin Li; Meiling Yin; Sen Zhang; Xiaoming Liu; Lisha Wang; Nini Wang; Lin Wang; Hideo Ema; Fang Dong (Stem Cell Reviews and Reports, 2026)

Bidirectional gut-heart axis interactions in the context of predictive, preventive, and personalised medicine: a time-course analysis of comorbidity and mortality risk in a large population cohort - Meiling Cao; Di Liu; Haotian Wang; Cancan Li; Huapeng Lin; Lijuan Wu; Youxin Wang (EPMA Journal, 2026)

Enhanced electrocatalytic degradation of concentrated simulated metronidazole wastewater by MIL-101(FeCu)/graphite felt electrodes - Songshan Jiang; Fan Wu; Rui Wen; Lin Xu; Qian Zhong; Meiling Yang; Bai He; Huan Yi; Huan Pang (Chemical Engineering Journal, 2026)

Tracing thallium pollution in arsenic mining/smelting areas using high-precision thallium isotopic composition - Xudong Wei; Shunlong Jiang; Jin Wang; Hangfei Guo; Dieyu Chen; Ke Lin; Meiling Yin; Wanpeng Chen; Yinyin Lu; Yurong Gao; Juan Liu (Applied Geochemistry, 2026)

The changes of antioxidant system, membrane integrity and phenolics metabolism participate in bongkrekic acid and adenosine triphosphate-mediated energy status regulating longan pericarp browning - Meiling Li; Hetong Lin; Ruiling Zhuo; Boqiang Li; Yifen Lin; Yihui Chen; Zhongqi Fan; Hui Wang (Postharvest Biology and Technology, 2026)

Bio-inspired fabrication of heterostructured porous core-shell PANI@Cu2O/CMC composite beads for green catalysis in A3 and decarboxylative A3 couplings - Shuyao Zhang; Ting Lin; Yuling Huang; Jiayi Huang; Meiling Xue; Zhihao Shan; Yiqun Li (Sustainable Chemistry and Pharmacy, 2025)

Changes in soil quality and crop productivity along rice cultivation chronosequences in saline-alkali soils - Bangyan Zhang; Jinmin Wu; Xiaolong Bai; Lei Li; Meiling Lin; Xing Xu; Fengju Zhang; Bin Wang (Journal of Environmental Management, 2025)

Efficient removal of antibiotics and synthetic dyes using VTMS-functionalized N/S-GQDs-PVA/cellulose composite aerogels - Muhammad Yousif; Meiling Zhang; Bilqees Hussain; Xupin Zhuang; Zhangang Wang; Hongxia Wang; Tong Lin (Chemical Engineering Journal, 2025)

DNP and ATP regulate disease progression in Neopestalotiopsis clavispora-infected guava fruit by modulating respiratory and energy metabolism - Hongbin Chen; Yifei Chen; Xuanjing Jiang; Yuzhao Lin; Yazhen Chen; Meiling Li; Yihui Chen (Postharvest Biology and Technology, 2025)

CO2 adsorption and separation properties of decorative paper impregnated with amino-functionalized cellulose nanofibers/waterborne acrylic resin - Xiaopin Bu; Qian Wei; Zhuoxin Liao; Yuding Zhu; Meiling Chen; Junhui Yang; Xiuzhen Lin; Donggyun Kim; Xiangyu Wang; Song Li; Jeonghun Kim; Wenkai Zhu (Chemical Engineering Journal, 2025)

Spatiotemporal variation of forest water conservation based on dual-variable calibration of runoff and evapotranspiration with SWAT model - Jiao Chen; Meiling Zheng; Feng Lin; Xingwei Chen; Huaxia Yao (Agricultural and Forest Meteorology, 2025)

Self-assembled mogroside v nanomicelle system improves oral bioavailability of the magnolol - Chengzhi Liu; Lingyi Ren; Niu Liu; Mengchu Niu; Yifei Xiang; Xianhua Wu; Changhua Lin; Zhengmin Liang; Meiling Yu; Jiakang He (Food Chemistry, 2025)

Comparative transcriptomic and metabolomic analyses reveal the role of acidic electrolyzed-oxidizing water in enhancing disease resistance in Phomopsis longanae Chi-infected longans - Meiling Li; Zhongqi Fan; Xiaoze Dai; Mengshi Lin; Yifen Lin; Hui Wang; Ruiling Zhuo; Yen-Con Hung; Hetong Lin; Yihui Chen (Postharvest Biology and Technology, 2025)

Ferrihydrite sulfidation transformation and coupled As(V) and Cd(II) mobilization under anoxic conditions - Xiaoming Zhao; Xu Ma; Yuyin Ma; Zidan Yuan; Shaofeng Wang; Yuanming Pan; Meiling Shi; Jinru Lin (Journal of Hazardous Materials, 2025)

Development of the novel formulations of perospirone for the treatment of schizophrenia - Zijun Zhang; Famin Ke; Jili Wu; Xiyao Li; Xin Chen; Lanxing Zhang; Pei Jing; Zerong Liu; Zhongbing Liu; Ruilin Lu; Shihua Fu; Meiling Zhou; et al. (Drug Delivery and Translational Research, 2025)

NIR-activated endoplasmic reticulum stress amplifier to regulate phagocytosis for macrophage-mediated cancer immunotherapy - Yaru Zhang; Wenyu Xie; Jiamin Luo; Rui Gao; Zhimin Gao; Xinyi Wang; Yongxin Huang; Chen Lin; Meiling Tan; Zhiyao Hou (Chemical Engineering Journal, 2025)

Anemarrhenae rhizoma combined with Trichosanthis radix ameliorated type 2 diabetes in rats via the PI3K-Akt signalling pathway based on network pharmacology analysis - Yan Lin; Jinde Zheng; Xinyi Zhao; Bei Zheng; Ying Li; Wenjuan Yang; Bing Han; Hanxiao Tang; Meiling Zhang (Natural Product Research, 2025)

Impact of humidity variations at different distances from the lake surface on rhizosphere microbiota of Trifolium repens L - Jin Chen; Meiling Ping; Xiaowan Geng; Keqing Lin; Boyan Wang; Yuxin Zhai; Yizhen Meng; Xiaoyu Li (Physiological and Molecular Plant Pathology, 2025)

Microscale fluvial landscape evolution and its impacts on early human settlement at the Shangshan cultural site in the upper Qiantang region, eastern China - Wenjia Zhang; Zhou Lin; Guoping Zhang; Leping Jiang; Meiling Chen; Shengchao Zhou; Yuchen Zhang; Xiang Zhao (Geomorphology, 2025)

Melatonin treatment maintains the quality properties and storability of carambola fruit by modulating energy metabolism - Ting Hu; Shaojie Zheng; Qingqing Liu; Meiling Li; Jingyuan Chen; Huili Zhang; Mengshi Lin; Hetong Lin; Yihui Chen (Food Chemistry, 2025)

Research on antibiotic resistance genes in wild and artificially bred green turtles (Chelonia mydas) - Xin Niu; Liu Lin; Ting Zhang; Xiaoyu An; Yupei Li; Yangfei Yu; Meiling Hong; Haitao Shi; Li Ding (Science of The Total Environment, 2024)

Exposure to butylparaben induces oxidative stress and apoptosis in the liver of Polypedates megacephalus tadpole - Xiaoqi Ai; Muhammad Shahid Iqbal; Rui Lin; Xia Wu; Lijun Wang; Meiling Hong (Frontiers in Marine Science, 2024)
Butylparaben (BuP) is a ubiquitous preservative in cosmetics, foods, and medicine. As an emerging pollutant, it has gained wide attention in recent years. Because amphibians have both aquatic and terrestrial life stages and high skin permeability, they are sensitive to environmental changes. To assess the toxic effects of BuP on amphibians, the present study was conducted on the spot-legged tree frog ( Polypedates megacephalus ) tadpoles. In the present study, LC 50 of BuP for 96 h exposures was 3509 µg/L. Then, the tadpoles were exposed to 0, 350 and 2100 µg/L BuP (hereafter named as CK, B1 and B2) for 12, 24 and 48 h, the oxidative stress and apoptosis in the liver were analyzed. The results showed that the content of MDA and activity of SOD and GSH-PX were increased with an increase in BuP exposure. BuP stress significantly altered the expression of Nrf2-Keap1 signal pathway genes. An increase in the expression of JAK-STAT signal pathway genes was observed with an increase in the exposure to BuP concentration at 24 and 48 h. In contrast, the expression of negative regulators of JAK-STAT signal pathway were significantly increased at 12 h and decreased at 24 and 48 h. A significant decrease in pro-apoptosis genes expression ( Bax and Caspase3 ) were observed at 12 h but increased at 24 and 48 h, while the expression of anti-apoptosis gene ( Bcl-2 ) decreased at 24 and 48 h. These results provide a valuable reference point for assessing the ecological and health risks associated with BuP in the environment.

Development of multi-cross-linking, rapid curing, and easy cleaning, edible hydrogels for meat preservation - Yuxin Cheng; Jiaxin Xu; Rongfan Zhang; Jianguo Lin; Meiling Zhou; Xianmin Qin; Keshan Wang; Ying Zhou; Qiujin Zhu; Yongguo Jin; Yuanyuan Liu (Food Hydrocolloids, 2024)

Occupation patterns during the Shangshan in the upper Qiantang River Basin, eastern China: A geomorphic study based on GIS - Wenjia Zhang; Zhou Lin; Leping Jiang; Chao Ding; Meiling Chen; Shengchao Zhou; Xiang Zhao (Quaternary International, 2024)

Acidic electrolyzed-oxidizing water treatment mitigated the disease progression in Phomopsis longanae Chi-infected longans by modulating ROS and membrane lipid metabolism - Meiling Li; Hetong Lin; Chao Wang; Yazhen Chen; Mengshi Lin; Yen-Con Hung; Yifen Lin; Zhongqi Fan; Hui Wang; Yihui Chen (Food Chemistry, 2024)

Seasonal changes in hepatic lipid metabolism and apoptosis in Chinese soft-shelled turtle (Pelodiscus sinensis) - Xiaoqi Ai; Rui Lin; Zeeshan Ali; Qingjun Zhu; Li Ding; Haitao Shi; Meiling Hong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Correction to: Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)

Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)
Although the functions of programmed death-1 (PD-1) on αβ T cells have been extensively reported, a role for PD-1 in regulating γδT cell function is only beginning to emerge. Here, we investigated the phenotypic and functional characteristics of PD-1-expressing γδT cells, and the molecular mechanism was also explored in the Plasmodium yoelii nigeriensis ( P. yoelii NSM)-infected mice . Flow cytometry and single-cell RNA sequencing (scRNA-seq) were performed. An inverse agonist of RORα, SR3335, was used to investigate the role of RORα in regulating PD-1 + γδT cells. The results indicated that γδT cells continuously upregulated PD-1 expression during the infection period. Higher levels of CD94, IL-10, CX3CR1, and CD107a; and lower levels of CD25, CD69, and CD127 were found in PD-1 + γδT cells from infected mice than in PD-1 − γδT cells. Furthermore, GO enrichment analysis revealed that the marker genes in PD-1 + γδT cells were involved in autophagy and processes utilizing autophagic mechanisms. ScRNA-seq results showed that RORα was increased significantly in PD-1 + γδT cells. GSEA identified that RORα was mainly involved in the regulation of I-kappaB kinase/NF-κB signaling and the positive regulation of cytokine production. Consistent with this, PD-1-expressing γδT cells upregulated RORα following Plasmodium yoelii infection. Additionally, in vitro studies revealed that higher levels of p-p65 were found in PD-1 + γδT cells after treatment with a RORα selective synthetic inhibitor. Collectively, these data suggest that RORα-mediated attenuation of NF-κB signaling may be fundamental for PD-1-expressing γδT cells to modulate host immune responses in the spleen of Plasmodium yoelii nigeriensis –infected C57BL/6 mice, and it requires further investigation.

Embryonic development and transcriptomic analysis in red-eared slider Trachemys scripta elegans under salinity stress - Jing Lin; Yuchen Kong; Haitao Shi; Meiling Hong; Li Ding (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

MnO2 nanozyme with lanthanide-based radiosensitization for advanced radiotherapy by tumor microenvironment triggering STING pathway activation - Meiling Tan; Zhimin Gao; Xiaozhao Wang; Chen Lin; Yuchi Wan; Wenyu Xie; Wei Chen; Yaru Zhang; Zewei Quan; Zhiyao Hou (Chemical Engineering Journal, 2024)

Morphological and transcriptomic analyses of embryonic development of red-eared slider Trachemys scripta elegans - Jing Lin; Miaomiao Zhang; Fangbin Liang; Yunfang Ni; Jiani Zhang; Haitao Shi; Meiling Hong; Li Ding (Animal Reproduction Science, 2024)

The role of energy transport system in pericarp browning of harvested longan fruit - Meiling Li; Hetong Lin; Yazhen Chen; Yihui Chen; Yifen Lin; Zhongqi Fan; Hui Wang (Postharvest Biology and Technology, 2024)

A Fe-Ni-MOF-74@bamboo photothermal evaporator for efficient solar steam generation - Yiduo Chen; Dongxu Gu; Yujuan Zhao; Chaowei Zhang; Meiling Li; Qi Zhou; Yonghui Lin; Yaru Gong; Zhongmin Su; Weiting Yang (Desalination, 2024)

Bilobetin attenuates Staphylococcus aureus virulence by targeting Von Willebrand factor-binding protein and staphylocoagulase - Chongling Zhang; Wenyuan Zhang; Shuyue Zhu; Chunjie Hu; Sihua Che; Meiling Wang; Mengli Jin; Nan Bian; Wu Song; Shuang Jiang; Yijing Jiang; Juan Hou; et al. (World Journal of Microbiology and Biotechnology, 2023)

Nanocomposite hydrogel to deliver the immunomodulator lenalidomide and anti-inflammatory hesperidin locally to joints affected by rheumatoid arthritis - Xingjie Du; Yan Lin; Zheyu Shuai; Junfeng Duan; Changguang Wang; Junsheng Liu; Jun Jiang; Jianming Wu; Meiling Zhou; Zhirong Zhang; Zhongbing Liu; Xiangyu Zhou; et al. (Chemical Engineering Journal, 2023)

Decomplexation of Ni-EDTA enhanced by Fe(III) reduction in the Fenton reaction: Insight into the role of carbonyl groups - Meiling Chen; Lin Ding; Shijun Zhu; Xiuqin Xiong; Xinkai Yuan; Yanhua Peng; Liming Yang; Hui Shi; Penghui Shao; Xubiao Luo (Journal of Environmental Chemical Engineering, 2023)

Reservoir water flooding evaluation based on electromagnetic wave logging permittivity and conductivity inversion - Yi Xiaodong; Zhang Meiling; Qin Lianbin; Lin Jianhua (Journal of Applied Geophysics, 2023)

Memristive competitive hopfield neural network for image segmentation application - Cong Xu; Meiling Liao; Chunhua Wang; Jingru Sun; Hairong Lin (Cognitive Neurodynamics, 2023)

An injectable antibacterial hydrogel to regulate ocular immune for endophthalmitis treatment - Zunzhen Ming; Lin Han; Huanhuan Zhu; Meiyu Bao; Qiangyuan Fan; Shaobo Xue; Kesheng Wang; Yue Zhang; Meiling Lu; Chongshun Xu; Qi Wu; Tingting Li; et al. (Chemical Engineering Journal, 2023)

Target and non-target analysis of organochlorine pesticides and their transformation products in an agrochemical-contaminated area - Di Huang; Lirong Gao; Shuai Zhu; Lin Qiao; Yang Liu; Qiaofeng Ai; Chi Xu; Wenwen Wang; Meiling Lu; Minghui Zheng (Chemosphere, 2023)

Regulatory role of myo-inositol in the ovarian development of female Chinese mitten crab (Eriocheir sinensis) - Xianyong Bu; Qincheng Huang; Ying Song; Changle Qi; Zhideng Lin; Xiaodan Wang; Meiling Zhang; Chuanjie Qin; Jian G. Qin; Liqiao Chen (Aquaculture, 2023)

Pharmacokinetics and residue elimination of metalaxyl enantiomers in snakehead (Channa argus) - Hao Zhou; Meiyu Zhang; Qi Shan; Heqing Huang; Meiling Zhang; Shugui Liu; Jiawei Lin; Lisha Ma; Guangming Zheng; Lichun Li; Cheng Zhao; Xiaoxin Dai; et al. (Aquaculture, 2023)

Acidic electrolyzed water treatment suppresses Phomopsis longanae Chi-induced the decreased storability and quality properties of fresh longans through modulating energy metabolism - Meiling Li; Qin Lin; Yazhen Chen; Yihui Chen; Mengshi Lin; Yen-Con Hung; Hetong Lin (Food Chemistry, 2023)

Can urban rail transit reduce haze pollution? A spatial difference-in-differences approach - Yumei Lin; Meiling Li; Ruofei Lin (Environmental Science and Pollution Research, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Does lower regional density result in less CO2 emission per capita? - Yumei Lin; Junpei Huang; Meiling Li; Ruofei Lin (Environmental Science and Pollution Research, 2022)

Exendin-4 Reversed the PC12 Cell Damage Induced by circRNA CDR1as/miR-671/GSK3β Signaling Pathway - Hui Quan; Qiudan Chen; Kesheng Wang; Qinwan Wang; Meiling Lu; Yue Zhang; Sujing Qiang; Shaobo Xue; Lin Han; Huanhuan Zhu; Qiangyuan Fan; Meiyu Bao; et al. (Journal of Molecular Neuroscience, 2021)

Genetic basis of maize ear angle revealed by high-density single nucleotide polymorphism markers in four recombinant inbred line populations - Jingwei Lin; Shoukun Li; Gengyuan Liang; Meiling Liu; Taicheng Jin; Zhengwei Qu; Haoge Li; Shuisen Chen; Cong Li; Ao Zhang; Yanye Ruan; Zhenhai Cui (Euphytica, 2020)

Two new monoterpene glucosides from Xanthium strumarium subsp. sibiricum with their anti-inflammatory activity - Hai Jiang; Xudong Xing; Meiling Yan; Xinyue Guo; Lin Yang; Liu Yang (Natural Product Research, 2019)

Investigation of Lactic Acid Bacteria Isolated from Giant Panda Feces for Potential Probiotics In Vitro - Qian Liu; Xueqin Ni; Qiang Wang; Zhirong Peng; Lili Niu; Meiling Xie; Yicen Lin; Yi Zhou; Hao Sun; Kangcheng Pan; Bo Jing; Dong Zeng (Probiotics and Antimicrobial Proteins, 2019)

Structure and geochronology of the Tongbai complex and their implications for the evolution of the Tongbai orogenic belt, central China - Huan Liu; Shoufa Lin; Chuanzhong Song; Meiling Wu (International Geology Review, 2017)

Characterization of BcMF23a and BcMF23b, two putative pectin methylesterase genes related to pollen development in Brassica campestris ssp. chinensis - Sue Lin; Li Huang; Xiaolin Yu; Xingpeng Xiong; Xiaoyan Yue; Tingting Liu; Ying Liang; Meiling Lv; Jiashu Cao (Molecular Biology Reports, 2017)

Estimation of residue depletion of cyadox and its marker residue in edible tissues of pigs using physiologically based pharmacokinetic modelling - Lingli Huang; Zhoumeng Lin; Xuan Zhou; Meiling Zhu; Ronette Gehring; Jim E. Riviere; Zonghui Yuan (Food Additives & Contaminants: Part A, 2015)

Pc4, a putative movement protein of Rice stripe virus, interacts with a type I DnaJ protein and a small Hsp of rice - Lianming Lu; Zhenguo Du; Meiling Qin; Ping Wang; Hanhong Lan; Xiaoqing Niu; Dongsheng Jia; Liyan Xie; Qiying Lin; Lianhui Xie; Zujian Wu (Virus Genes, 2009)